ESTABLSHMENT OF CELL LINE DERIVED FROM EMBRYONIC TISSUE OF THE DLAMONDBACK MOTH, plutella xylostella (L.) - Petcharawan*, O.; Mongkolpoch, K.; Belloncik, S. (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
A new cell line designated KMITL-PX-E1 has been established from embryonic tissue of the diamondback moth, Plutella xylostella (L.). The primary cultures were seeded in TNM-FH medium supplemented with 20% fetal bovine serum and incubated at 28 °C. After the 18th passage, the cultures were adapted and maintained in TNM-FH medium supplemented with 10% fetal bovine serum. The cell line consisted of a mixture of two cell types, spindle-shaped cells and epithelial-like cells, both of them grew as attached monolayer. The population doubling time at the 2nd and the 18th passages were 110.59 and 61.22 hrs, respectively. The chromosome numbers varied from 6-124. Random amplified polymorphic DNA profile analysis showed that the diamondback moth cell line (KMITL-PX-E1) profile differed from the profiles of the beet armyworm (SE-1) and the American cotton bollworm (KMITL-HA-E1) cell lines maintained in the laboratory. KMITL-PX-E1 cell line supported replication of Autographa californica (AcMNPV) and Exoa scandens cytoplasmic polyhedrosis virus (EsCPV). However, this cell line was sensitive to Bacillus thuringiensis toxin. Keywords: Plutella xylostella cell line, diamondback moth, nucleopolyhedrovirus, cytoplasmic polyhedrosis virus, Random amplified polymorphic DNA Corresponding author: E-mail: ksounrua@kmitl.ac.th